A new device for propulsion analysis in swimming - Lanotte, N.; Annino, G.; Bifaretti, S.; Gatta, G.; Romagnoli, C.; Salvucci, A.; Bonaiuto, V. (Proceedings, 2018)
The mechanism of propulsion in swimming has been widely researched in recent years, but not completely clarified. While it is obvious that the movement of arms provides most of the thrust, it is unclear how each phase of the stroke translates into body acceleration. Investigation is carried out mainly by video analysis or using Inertial Measurement Units (IMUs) which do not measure forces. In this paper, we present a wearable data acquisition system for swimmers. The system is composed of two instrumented paddles, measuring the pressure difference between palm and back of the hands, and an IMU. The paddles provide information about the forces that cause propulsion, while the IMU measures the effects of these forces. Data are acquired by a microcontroller unit placed in waterproof case at the athlete`s waist, and transferred to PC via a Bluetooth link. Early experimental data are presented.